Capability analysis of electability candidate member DPRD DKI Jakarta Party Nasdem - Yehezkiel, Niko; B. Sukamdani, Hariyadi; Diyah Maharani, Maya Dewi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The human resource factor is an element that must be considered by the organization or company. Political parties are present in society with the aim of seeking and maintaining power in order to realize the program. The purpose of this study was to obtain an overview of the electability of the Nasdem party in DKI Jakarta in terms of capability evaluation, and the purpose of this study was to analyze the electability of candidates for DPRD DKI Jakarta members. Jakarta, NasDem Party. The research method used is descriptive research with qualitative and quantitative approaches. The population sample used in this study amounted to 40 people and was for data analysis using SPSS and ISM. The results of the study show that capability has a positive and significant effect on electability. The benchmark factor for success is the capability of sector 1 (autonomy). It has three factors. The objective ability factor is where sector 1 (autonomous) has 3 factors; capabilities constraints, where sector 1 (autonomous) has 2 factors. HR is an important part of building integrity, realizing the vision and mission of an organization. The connection between human resources and skills is more important than just making people more electable temporarily.